Assessment of the Short-Term Fertilizer Potential of Mealworm Frass Using a Pot Experiment - Houben, David; Daoulas, Guillaume; Dulaurent, Anne-Maïmiti (Frontiers in sustainable food systems, 2021)
The forecasted growth of insect production in the next few years will generate high quantities of frass (insect excreta). Although frass is increasingly considered a potential fertilizer, the dynamics of nutrient supply by frass is still poorly understood. Here, we aimed at gaining insight into the short-term fertilizer value of frass from mealworm ( Tenebrio molitor L.) in order to optimize its sustainable use in agroecosystems. Using a short-term pot experiment, we showed that, even though frass has a great potential to be used as a substitute of mineral NPK fertilizer, its N fertilizer potential is mediated by its rate of application. At 10 t ha −1 , due to its fast mineralization coupled with improvement in microbial activity (assessed using Biolog EcoPlate), frass was as effective as mineral fertilizer to supply N to plant. By contrast, at 5 t ha −1 , the lower frass mineralization induced a reduced N uptake compared to its mineral control. Unlike N, frass was as effective as mineral fertilizer to supply P and K to plants irrespective of its application rate. This was attributed to the presence of P and K in a readily available form in frass. Taken together, our results indicate that mealworm frass supplies very rapidly N, P and K to plants but its effects on N dynamics should be better investigated to warrant its sustainable use as an alternative fertilizer for managing NPK nutrition in cropping systems.